2009
DOI: 10.1097/aln.0b013e3181ab6743
|View full text |Cite
|
Sign up to set email alerts
|

Moderate Exposure to Allogeneic Blood Products Is Not Associated with Reduced Long-term Survival after Surgery for Coronary Artery Disease

Abstract: Background: It has been suggested that blood transfusion has an adverse effect on long-term health, mainly through immune modulation and tumor promotion. To further assess this concern, the authors have performed a prospective observational study with the hypothesis that after taking perioperative risk factors relevant to long-term survival into account, patients undergoing coronary artery surgery who receive a perioperative allogeneic blood transfusion have worse long-term survival than those who do not.Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 21 publications
1
16
0
1
Order By: Relevance
“…Full articles were retrieved for 45 studies; 13 further studies were excluded as they did not fulfil our eligibility criteria (see online supplementary appendix 2 for list of excluded studies). Thirty-two studies were included in the review; 23 7-30 studies assessed the effects of RBCT versus no RBCT, 5 studies [31][32][33][34][35] assessed different volumes of RBCT and 4 [36][37][38][39] assessed giving older versus newer RBCT (see figure 1). …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Full articles were retrieved for 45 studies; 13 further studies were excluded as they did not fulfil our eligibility criteria (see online supplementary appendix 2 for list of excluded studies). Thirty-two studies were included in the review; 23 7-30 studies assessed the effects of RBCT versus no RBCT, 5 studies [31][32][33][34][35] assessed different volumes of RBCT and 4 [36][37][38][39] assessed giving older versus newer RBCT (see figure 1). …”
Section: Resultsmentioning
confidence: 99%
“…Volume 'A' red blood versus volume 'B' red blood cells Five studies [31][32][33][34][35] assessed the effects of different volumes of RBCT on mortality. One of these studies 35 included both RBCT and other blood products.…”
Section: Presentation Of Adjusted and Unadjusted Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A transfusion volume of greater than 3 units was an independent predictor of early mortality but did not appear to affect long-term mortality. Conversely, Weightman et al [31], in a study of more than 1800 patients, just more than 1000 of whom were transfused, found that transfusion of less than 6 units of PRBC was not [32] and Veenith et al [33] have determined that PRBC transfusion in this patient population is an independent risk factor not only for increased mortality but also for prolonged intensive care unit length of stay. Most recently, a randomized, prospective trial of more than 500 patients, the Transfusion Requirements After Cardiac Surgery Study, comparing a "liberal" transfusion arm (keeping Hct N 30%) and a "restrictive" arm (transfusing only when Hct fell to b24%), has been published [34].…”
Section: Mortality In Patients Undergoing Cardiac Surgery and Receivimentioning
confidence: 94%
“…∆εδοµένα πολλών µελετών υποστηρίζουν ότι οι µεταγγίσεις αίµατος σχετίζονται µε αυξηµένη θνησιµότητα και θνητότητα στις καρδιοχειρουργικές επεµβάσεις [891,892]. Παρόλα αυτά, µια πρόσφατη µεγάλη µελέτη παρατήρησης δεν έδειξε κάποια σχέση µεταξύ µιας µέτριας (≤6 µονάδες) χρήσης παραγώγων αίµατος και ελάττωσης της επιβίωσης µακροπρόθεσµα [893]. Καθώς ο κίνδυνος για ανεπιθύµητα συµβάντα που σχετίζονται µε τη µετάγγιση είναι δυνατόν να συνδέεται µε το ποσοστό αυτής [894], η µείωση των µεταγγίσεων θεωρείται ένας σηµαντικός στόχος στις καρδιοχειρουργικές επεµβάσεις, άµεσα συνδεόµενος µε αυτές.…”
unclassified